2018
DOI: 10.12659/msm.907808
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNAs Serve as Diagnostic Biomarkers of Preeclampsia and Modulate Migration and Invasiveness of Trophoblast Cells

Abstract: BackgroundLong non-coding RNAs (lncRNAs) have emerged as crucial regulators of tumor progression. However, the effects of lncRNAs in preeclampsia are not entirely clear. The aim of this study was to demonstrate the potential of lncRNAs to serve as biomarkers in preeclampsia.Material/MethodsThe RNA expression levels of lncRNAs (NR_027457, BC030099, AF037219, NR_024178, AF085938, G43016, G36948, NR_029420, NR_024015, AK002210, NR_026643, and AL049277) in the serum of patients with preeclampsia and in the serum o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 44 publications
2
13
0
Order By: Relevance
“…The role of lncRNAs in regulation of cellular processes, including cell growth, proliferation, apoptosis, cell cycle, migration, invasion, differentiation, and others is well‐known . Several lncRNAs have been reported to affect cellular processes of trophoblast cells, including MVIH, TUG1, PVT1, Uc.187 , and MEG3 . In our study, we found that upregulation of PVT1 enhanced cell viability and promoted cell proliferation and migration of HRT8 cells, while PVT1 suppression repressed cell viability, cell proliferation, and migration.…”
Section: Discussionsupporting
confidence: 50%
“…The role of lncRNAs in regulation of cellular processes, including cell growth, proliferation, apoptosis, cell cycle, migration, invasion, differentiation, and others is well‐known . Several lncRNAs have been reported to affect cellular processes of trophoblast cells, including MVIH, TUG1, PVT1, Uc.187 , and MEG3 . In our study, we found that upregulation of PVT1 enhanced cell viability and promoted cell proliferation and migration of HRT8 cells, while PVT1 suppression repressed cell viability, cell proliferation, and migration.…”
Section: Discussionsupporting
confidence: 50%
“…The mechanisms underlying PE might be caused by the dysregulation of LOC284100, LOC391533, and CEACAMP8 [ 22 ]. The lncRNAs AF085938 and NR_027457 were found to be upregulated significantly, while AK002210 and G36948 were downregulated in PE, and all of them had vital diagnostic values for the PE detection [ 39 ]. Overall, more studies focused on differential lncRNAs in PE, will result I more effective treatments found for PE.…”
Section: Discussionmentioning
confidence: 99%
“…They found that misregulation of LOC391533, LOC284100 and CEACAMP8 might contribute to the mechanism underlying PE. In another lncRNA study, Luo and Li [19] indicated that NR_027457 and AF085938 were significantly up-regulated, whereas G36948 and AK002210 were significantly down-regulated in PE using the qRT-PCR method. They also found NR_027457, AF085938, G36948 and AK002210 had potential diagnostic value for the detection of PE.…”
Section: Discussionmentioning
confidence: 99%